Egg-spot matching in common cuckoo parasitism of the oriental reed warbler: effects of host nest availability and egg rejection. Issue 1 (December 2016) - Li, Donglai; Ruan, Yanan; Wang, Ying; Chang, Alan; Wan, Dongmei; Zhang, Zhengwang
Abstract Background The success of cuckoo parasitism is thought to depend largely on the extent of egg matching between cuckoo and host eggs, since poor-matching cuckoo egg would lead to more frequent egg rejection by the host. In this study, we investigated how egg-spot matching between the Common Cuckoo (Cuculus canorus ) and its host, the Oriental Reed Warbler (Acrocephalus orientalis ) is affected by the local parasitism rate, nest availability in breeding synchronization and egg rejection. Methods We used the paired design of parasitized and their nearest non-parasitized nests where breeding occurred simultaneously to compare egg-spot matching. The image analysis was used to compare four eggshell pattern variables, namely spot size, density, coverage on the different areas of egg surface, and the distribution on the whole egg surface. Egg recognition experiments were conducted to test the effect of egg spots on egg rejection by the host. Results Our results show that much better matching in almost all spot parameters tested on the side of the egg and the spot distribution on the whole egg occurred in parasitized nests than in non-parasitized nests. Matching of spot density between cuckoo and host eggs in parasitized nests increased with the synchronization between temporal availability of nests and the egg-laying period of female cuckoos. Egg recognition experiments in which the warbler eggs were deliberately painted with extra spots led to a significantly higher egg rejection rate (78.3%) than of unpainted eggs. Conclusion Our data suggest that both the high temporal encounter rate between cuckoo and warbler nests as well as the high egg rejection ability of the host are important factors for egg-spot matching of the cuckoos.